Stock Market Integration: Are Risk Premiums of International Assets Equal? - Setiawan, Kusdhianto (Gadjah Mada International Journal of Business, 2014)
This paper studies previous research on capital market integration and applies a simple international capital asset pricing model by considering the incompleteness in market integration and heteroscedasticity of the market returns. When we disregarded those two factors, we found that stock markets were integrated and the law of one price on risk premiums prevails. However, when the factors were considered, the markets were just partially integrated.